2018
DOI: 10.1002/pi.5707
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α′‐/α‐crystal polymorphism on properties of poly(l‐lactic acid)

Abstract: Poly(l‐lactic acid) (PLLA) is a biodegradable and biocompatible thermoplastic polyester produced from renewable sources, widely used for biomedical devices, in food packaging and in agriculture. It is a semicrystalline polymer, and as such its properties are strongly affected by the developed semicrystalline morphology. As a function of the crystallization temperature, PLLA can form different crystal modifications, namely α′‐crystals below about 120 °C and α‐crystals at higher temperatures. The α′ modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 167 publications
12
74
0
Order By: Relevance
“…S3 for details) is recorded for t c < 60 min, as highlighted by the solid blue curve. For t c > 60 min the exothermic signal of the reorganization of α'À to αÀ crystals is detected before melting [59][60][61][62]. This shows, as expected, that the crystallization at T g þ 20 � C induces α'À crystals.…”
Section: Impact Of the Annealing On The Amorphous Fractions Charactersupporting
confidence: 80%
“…S3 for details) is recorded for t c < 60 min, as highlighted by the solid blue curve. For t c > 60 min the exothermic signal of the reorganization of α'À to αÀ crystals is detected before melting [59][60][61][62]. This shows, as expected, that the crystallization at T g þ 20 � C induces α'À crystals.…”
Section: Impact Of the Annealing On The Amorphous Fractions Charactersupporting
confidence: 80%
“…The α'-crystal with loose pack manner is not thermally stable and could reorganize into a more-order α'-structure. 36 It is evident from Figure 4(a) that the presence of high-loading TNPP (2 wt%) facilitates the rearrangement of PLA chains in the α'-crystals to form the more-order α'-crystals during DSC heating scan. The crystals with more-order structure are then melted at a higher temperature of 153.4 C. However, the high-perfection α-crystals are unlikely developed through the crystallization conditions used in this study since no peak around 185 C due to the melting of α-crystal 37 is observed from our DSC melting thermograms of Figure 4(a).…”
Section: Thermal and Mechanical Propertiesmentioning
confidence: 99%
“…Several bio-based and/or biodegradable polymers have been developed commercially, such as polyhydroxyalcanoates, poly( l -lactic acid) (PLLA), polycaprolactone and polybutylene succinate and their derivates [ 2 ]. Among those listed, PLLA gained the greatest attention due to its numerous advantages such as being biodegradable and compostable, having good stiffness and strength and being able to be produced on a large scale by microbial fermentation of agricultural byproducts [ 1 , 3 , 4 ]. Besides its advantages, PLLA has also some drawbacks, mainly brittleness and slow crystallization kinetics that should be overcome to further develop its application possibilities [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%